Implementation of The Talaqqi Method in Memorizing Juz 'Amma for Group B Students At Uwais Al Qorny Tahfidz Qur'an Kindergarten - Nurmaya, Lisa; Choiriyah, Choiriyah; Priyanti, Nina Yuminar (CV. Creative Tugu Pena, 2025)
This descriptive qualitative research aimed to determine the implementation and effectiveness of the Talaqqi Method in improving the ability of Group B children to memorize Juz' Amma at the Uwais Al Qorny Tahfidz Qur'an Kindergarten, Bekasi City. Data was collected through observation, interviews, and documentation, with validity tested using data triangulation and credibility checks. The research results indicate that Uwais Al Qorny Tahfidz Qur'an Kindergarten actively uses the Talaqqi Method and found it easy to implement and proven effective in boosting children's memorization skills due to its continuous and repetitive nature. While hindering factors included student health and attendance, the primary success factor for its implementation was the full support from the school administration and the parents. Overall, this study affirms that the Talaqqi Method is an appropriate approach for teaching Juz' Amma memorization to early childhood students.